Estimating Stock Market Betas via Machine Learning - Drobetz, Wolfgang; Hollstein, Fabian; Otto, Tizian; Prokopczuk, Marcel (Journal of Financial and Quantitative Analysis, 2025)
Abstract Machine learning-based stock market beta estimators outperform established benchmark models both statistically and economically. Analyzing the predictability of time-varying market betas of U.S. stocks, we document that machine learning-based estimators produce the lowest forecast and hedging errors. They also help to create better market-neutral anomaly strategies and minimum variance portfolios. Among the various techniques, random forests perform the best overall. Model complexity is highly time-varying. Historical stock market betas, turnover, and size are the most important predictors. Compared to linear regressions, allowing for nonlinearity and interactions significantly improves predictive performance.